TIPE VERBA BAHASA GALELA - WADUI, SERLINDA FENI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Every word in the sentence has three classifications namely, syntactic category, syntactic functions and semantic roles. This research is related to the verb in the language Galela. This in the syntactic category serves as predicate verbs that require many types of arguments that must be present in the verb construction. Verb arguments it is located can be moved, that means the position of verbs in Galela not rigid in the sentence. On the role of semantic diverse grouping is applied, used nine kinds of semantic roles among actors, goals, experience, luck, place, tools, time, attributes and results. This study uses Sudaryanto (1993 ), data used in this study were taken from written sources of the biblical book Galela language, all of which are written using language Galela. From the available data the writer also speakers Galela who acted as an informant in dissecting or decipher Keywords : Verb, Galela language